A Purely Sequential Estimation Procedure for the Parameter of U(θ, mθ) Distribution. Issue 3 (September 2014) - Patil, H.S.
Abtsrcat: In the literature, an extensive work on sequential fixed width confidence interval (CI) for the parameter of U(0, θ) model is available. In this article we propose a fixed width (1-) level sequential CI for the parameter θ of U(θ, mθ) distribution, where m > 1 is known, based on the large-sample approximation of coverage probability.